Key Challenges and Strategies Towards Sustainable Infrastructure Development in Malaysia - Mustaffa, Nur Kamaliah; Nor Shahrudin, Nur Shuhada; Abdul Aziz, Mohd Feisal Hafiz; Mustaffa, Aminuddin (International Journal of Integrated Engineering, 2023)
The world is fixated on climate change because of its damage to the environment and the ripple effect it can have on people's health and the economy. This study aims to delve into research focusing on sustainable infrastructure development in Malaysia, as well as the main obstacles and approaches to taking on such a task. This study used a mixed-methods system, which allowed for the collection a large amount of data and made it easy to compare results from different settings. The study found that more people are aware of sustainable impact assessment in infrastructure projects and familiar with resilient, sustainable development than sustainable performance evaluation. The studies also showed that the main problems in implementing sustainability include minimising adverse hazards, financial and budget investment issues, as well as inadequate governance and management. The proposed measures are broken down into monetary, institutional, and organisational themes. Possible steps toward a more sustainable infrastructure involve increasing green investment and financing, fostering green policies and environmental regulations, promoting green technologies and materials, and growing capacity through improved awareness and training. The findings of this study provide construction stakeholders with insight into an analysis of existing methodologies and strategies for integrating sustainable infrastructure development. Resolving obstacles and refining implementation tactics facilitated the effectiveness of the transformation towards a more sustainable infrastructure.